Aging in Context: Incorporating Everyday Experiences Into the Study of Subjective Age - Hughes, Matthew L.; Touron, Dayna R. (Frontiers in Psychiatry, 2021)
The age that a person feels is a strong predictor of their well-being and long-term health, beyond chronological age, showing that people have a self-awareness that provides insight into their aging process. It appears this insight has broad implications for a person’s everyday life and functioning. One’s subjective age is shaped by metacognitive beliefs about aging, including both expectations about typical changes but most notably the awareness and interpretation of personal experiences. Subjective age has been described as multidimensional, aligning with life domains such as cognitive, social, and physical functioning. This perspective, coupled with laboratory studies that manipulate subjective age, suggests that situational context has an important role in determining the age a person feels. Here we review literature on subjective age with a focus on how research and theoretical perspectives should be adapted to integrate momentary experiences. We propose a contextual model that will help discriminate the links between situational influences and subjective age, as well as resulting behaviors that impact health and well-being. While most research has considered subjective age to be a relatively stable variable, we provide a novel account of how daily life offers a variety of situational contexts and experiences that directly impact the age a person feels at a given moment. We propose that studying moment-to-moment context is a critical next step in understanding the associations between subjective age, lifestyle choices, and health outcomes.